Proceedings of the 38th International Symposium on Lattice Field Theory — PoS(LATTICE2021) 2022
DOI: 10.22323/1.396.0367
|View full text |Cite
|
Sign up to set email alerts
|

Continuum extrapolation of the gradient-flowed color-magnetic correlator at $1.5\,T_c$

Abstract: In a recently published work we employ gradient flow on the lattice to extract the leading contribution of the heavy quark momentum diffusion coefficient in the heavy quark limit from calculations of a well-known two-point function of color-electric field operators. In this article we want to report the progress of calculating the recently derived color-magnetic correlator that encodes a finite mass correction to this transport coefficient. The calculations we present here are based on the same ensemble of que… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The colour-magnetic contribution experiences non-trivial renormalization [14], but otherwise its lattice determination should not be harder than for the colour-electric case. Indeed attempts in this direction have been initiated by several groups recently [15,16].…”
Section: Jhep08(2022)128mentioning
confidence: 99%
“…The colour-magnetic contribution experiences non-trivial renormalization [14], but otherwise its lattice determination should not be harder than for the colour-electric case. Indeed attempts in this direction have been initiated by several groups recently [15,16].…”
Section: Jhep08(2022)128mentioning
confidence: 99%
“…Heavy quark diffusion coefficient with gradient flow Viljami Leino Banerjee 2012 [9] Francis 2015 [10] Altenkort 2021 [18] Brambilla 2020 [11] Banerjee 2022a [12] Banerjee 2022b [13] Brambilla 2022 [20] Figure 5: Our result of 𝜅 E (Grey diamond) compared to existing lattice results.…”
Section: Pos(lattice2022)183mentioning
confidence: 99%
“…The heavy quark diffusion coefficient 𝜅 E,B has been measured with gradient flow in Refs. [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in the heavy quark mass limit can be found in [18][19][20][21][22][23] in both quenched approximation and (2+1)-flavor lattice QCD. Accessing the first mass suppressed correction to the diffusion coefficient are also attempted [22,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%